Business Proposal to Setup the Fruit Juice Bar in Abuja (Global Journal of Management and Business Research, 2019)
Business ideas should rely on the development of the innovative concept to guarantee long term relationships with the customers and providing them value and satisfaction to retain them. This study has been conducted with an aim of examining the feasibility to set up a fruit juice bar concept in Abuja, Nigeria. It uses survey method and regression analysis for the purpose of testing and a sample size of almost 100 people in Abuja was taken and according to the results, while discussing on previews work